TP53 Mutations and Survival in Squamous-Cell Carcinoma of the Head and Neck - Poeta, M. Luana (2007)
BACKGROUND: The abrogation of function of the tumor-suppressor protein p53 as a result of mutation of its gene, TP53, is one of the most common genetic alterations in cancer cells. We evaluated TP53 mutations and survival in patients with squamous-cell carcinoma of the head and neck. METHODS: A total of 560 patients with squamous-cell carcinoma of the head and neck who were treated surgically with curative intent were enrolled in our prospective multicenter, 7-year study. TP53 mutations were analyzed in DNA from the tumor specimens with the use of the Affymetrix p53 chip and the Surveyor DNA endonuclease and denaturing high-performance liquid chromatography. Mutations were classified into two groups, disruptive and nondisruptive, according to the degree of disturbance of protein structure predicted from the crystal structure of the p53–DNA complexes. TP53 mutational status was compared with clinical outcome. RESULTS: TP53 mutations were found in tumors from 224 of 420 patients (53.3%). As compared with wild-type TP53, the presence of any TP53 mutation was associated with decreased overall survival (hazard ratio for death, 1.4; 95% confidence interval [CI], 1.1 to 1.8; P = 0.009), with an even stronger association with disruptive mutations (hazard ratio, 1.7; 95% CI, 1.3 to 2.4; P<0.001) and no significant association with nondisruptive mutations (hazard ratio, 1.2; 95% CI, 0.9 to 1.7; P = 0.16). In multivariate analyses a disruptive TP53 alteration, as compared with the absence of a TP53 mutation, had an independent, significant association with decreased survival (hazard ratio, 1.7; 95% CI, 1.2 to 2.4; P = 0.003). CONCLUSIONS: Disruptive TP53 mutations in tumor DNA are associated with reduced survival after surgical treatment of squamous-cell carcinoma of the head and neck.